2008
DOI: 10.1002/app.29117
|View full text |Cite
|
Sign up to set email alerts
|

Rubber/LDH nanocomposites by solution blending

Abstract: The rubber nanocomposites containing ethylene vinyl acetate (EVA) having 60 wt % of vinyl acetate content and organomodified layered double hydroxide (DS-LDH) as nanofiller have been prepared by solution intercalation method and characterized. The XRD and TEM analysis demonstrate the formation of completely exfoliated EVA/DS-LDH nanocomposites for 1 wt % filler loading followed by partially exfoliated structure for 5-8 wt % of DS-LDH content. EVA/DS-LDH nanocomposites show improved mechanical properties such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Kuila et al reported epoxy/graphene oxide nanocomposites. The pure epoxy resin had very poor thermal conductivity, but the addition of 1% graphene oxide significantly enhanced the thermal conduction and the performance was similar to composite with 1% of single wall nanotubes.…”
Section: Polymer/graphene Nanocompositesmentioning
confidence: 99%
“…Kuila et al reported epoxy/graphene oxide nanocomposites. The pure epoxy resin had very poor thermal conductivity, but the addition of 1% graphene oxide significantly enhanced the thermal conduction and the performance was similar to composite with 1% of single wall nanotubes.…”
Section: Polymer/graphene Nanocompositesmentioning
confidence: 99%
“…This in all probability is due to the fact that the improvement in the mechanical strength of a composite depends on effective stress transfer from polymer to nanofiller, whereas the thermal stability is guided by the chemical nature of the polymer, the type of filler and the modification route of the nanofiller. Earlier work in the literature also confirmed that the maximum improvements in mechanical and thermal properties are not proportionally related with respect to the filler loadings in the polymer matrix 8, 48–50…”
Section: Resultsmentioning
confidence: 74%
“…Recently, polymer=layered double hydroxide (LDH) NCs have been studied extensively for their remarkable improvement in the mechanical properties, thermal stability, reduced gas permeability, and flame retardancy compared with virgin polymers and traditional organicinorganic composites [12][13][14][15][16][17] . This is mainly due to the effective dispersion of LDH layers of nanometer thickness with the aspect ratios of about 30-100 within the polymer matrix [18] .…”
Section: Introductionmentioning
confidence: 99%